2022
DOI: 10.1002/lary.30523
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endoscopic Modified and Typical Myringoplasty: A Randomized Controlled Trial

Abstract: ObjectiveHere, we aimed to compare the operation time, postoperative pain score, graft healing, graft success rate, cholesteatoma incidence, audiometric outcomes, and complications between endoscopic modified myringoplasty (EMM) and endoscopic typical myringoplasty (ETM).MethodsPatients with unilateral chronic tympanic membrane (TM) perforations undergoing myringoplasty were prospectively randomized to undergo EMM (n = 44) or ETM (n = 45). The operation time, postoperative pain score, graft healing, graft succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is traditional to remove scar tissue from the perforation margins prior to myringoplasty; the suggestion is that nonremoval would lower the graft success rate 5,7,21,22 . Our recent studies showed that the absence of perforation rimming did not compromise graft success 10,23 . The present study is novel in that it is the first to compare the graft outcomes and early graft neovascularization after underlay myringoplasty without rimming the perforation with or without lateral graft packing.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is traditional to remove scar tissue from the perforation margins prior to myringoplasty; the suggestion is that nonremoval would lower the graft success rate 5,7,21,22 . Our recent studies showed that the absence of perforation rimming did not compromise graft success 10,23 . The present study is novel in that it is the first to compare the graft outcomes and early graft neovascularization after underlay myringoplasty without rimming the perforation with or without lateral graft packing.…”
Section: Discussionmentioning
confidence: 84%
“…5,7,21,22 Our recent studies showed that the absence of perforation rimming did not compromise graft success. 10,23 The present study is novel in that it is the first to compare the graft outcomes and early graft neovascularization after underlay myringoplasty without rimming the perforation with or without lateral graft packing. We confirmed that underlay myringoplasty with no perforation rimming and no lateral graft packing did not affect the long-term graft outcomes.…”
Section: Discussionmentioning
confidence: 99%